Increase in receptor activator of nuclear factor κB ligand/osteoprotegerin ratio in peri-implant gingiva exposed to Porphyromonas gingivalis lipopolysaccharide - Takahiro Shuto; Takanori Wachi; Yoshinori Shinohara; Hiroki Nikawa; Seicho Makihira (Elsevier, 2016)
Background/purpose: The prevalence of peri-implant diseases, including peri-implant mucositis and peri-implantitis, is increasing. The aim of this study was to elucidate the pathological mechanisms of inflammation and alveolar bone resorption in peri-implant tissues. To do this, we fabricated inflamed gingiva around mini-implants in the palatine processes of rats using lipopolysaccharide derived from Porphyromonas gingivalis (P.g-LPS). Materials and methods: Pure titanium mini-implants were implanted into the palatine processes of rats, and then intermittent injections of P.g-LPS were made into the gingival tissues surrounding the mini-implants. The expression patterns of tumor necrosis factor-α, interleukin-1β, chemokine (C-C motif) ligand 2, receptor activator of nuclear factor κB ligand (RANKL), and osteoprotegerin (OPG) in the tissues were examined using real-time reverse transcriptase polymerase chain reaction or enzyme-linked immunosorbent assays. Immunohistochemical analysis was also performed to compare the T and B cells expressing RANKL. Results: P.g-LPS increased the expressions of tumor necrosis factor-α, interleukin-1β, chemokine (C-C motif) ligand 2, and RANKL in the gingival tissues surrounding the mini-implants. In contrast, the expression of OPG in the P.g-LPS samples was decreased. Consequently, the RANKL/OPG ratio was significantly increased. Moreover, cells stained positively for both anti-CD3 and anti-RANKL antibodies were only found in the samples treated with P.g-LPS. Conclusion: These data revealed that P.g-LPS injections increased the RANKL/OPG ratio in the gingival tissues surrounding mini-implants in the rat model. In addition, the CD3-positive cells in the gingival tissues injected with P.g-LPS expressed RANKL. This suggests that the activated T cells capable of infiltrating gingival tissues affected by P.g-LPS may be one of the sources of RANKL and may also be involved in the disease progression from peri-implant mucositis to peri-implantitis.